Airway basal cells from human-induced pluripotent stem cells: a new frontier in cystic fibrosis research - Demchenko, Anna; Belova, Lyubava; Balyasin, Maxim; Kochergin-Nikitsky, Konstantin; Kondrateva, Ekaterina; Voronina, Ekaterina; Pozhitnova, Victoria; Tabakov, Vyacheslav; Salikhova, Diana; Bukharova, Tatiana; Goldshtein, Dmitry; Kondratyeva, Elena; et al. (Frontiers in Cell and Developmental Biology, 2024)
Human-induced airway basal cells (hiBCs) derived from human-induced pluripotent stem cells (hiPSCs) offer a promising cell model for studying lung diseases, regenerative medicine, and developing new gene therapy methods. We analyzed existing differentiation protocols and proposed our own protocol for obtaining hiBCs, which involves step-by-step differentiation of hiPSCs into definitive endoderm, anterior foregut endoderm, NKX2.1+ lung progenitors, and cultivation on basal cell medium with subsequent cell sorting using the surface marker CD271 (NGFR). We derived hiBCs from two healthy cell lines and three cell lines with cystic fibrosis (CF). The obtained hiBCs expressed basal cell markers (NGFR, KRT5, TP63) and could differentiate into lung organoids (LOs). We demonstrated that LOs derived from hiBCs can assess CFTR channel function using the forskolin-induced swelling assay. We also carried out non-viral (electroporation) and viral (recombinant adeno-associated virus (rAAV) serotypes 6 and 9, and recombinant adenovirus (rAdV) serotypes 5) transgene delivery to hiBCs and showed that rAAV serotype 6 is most effective against hiBCs, potentially applicable for gene therapy research.